2020
DOI: 10.3390/rs12223719
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Measured Incoming Shortwave and Longwave Radiation on a Glacier Surface with Estimated Records from Satellite and Off-Glacier Observations: A Case Study for the Forni Glacier, Italy

Abstract: The development of methods for quantifying meltwater from glaciated areas is very important for better management of water resources and because of the strong impact of current and expected climate change on the Alpine cryosphere. Radiative fluxes are the main melt-drivers, but they can generally not be derived from in situ measures because glaciers are usually located in remote areas where the number of meteorological stations is very low. For this reason, focusing, as a case study, on one of the few glaciers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Allen et al (2019) [19] suggested that fibers up to 750 µm and fragments ≤ 300 µm can reach remote areas through atmospheric transportation. Ambrosini et al (2019) [18] were the first to verify the presence of microplastics in an Alpine glacier environment (the Forni Glacier, a wide valley glacier located in the Italian Alps [20,21]), detecting concentrations comparable with those previously found in marine and coastal areas [18]. Crosta et al (2022) [22] found microplastics on other glaciers in the Italian Alps [22], suggesting the urgent necessity of actions to reduce the spread of microplastics in mountain glacierized areas.…”
Section: Introductionmentioning
confidence: 58%
“…Allen et al (2019) [19] suggested that fibers up to 750 µm and fragments ≤ 300 µm can reach remote areas through atmospheric transportation. Ambrosini et al (2019) [18] were the first to verify the presence of microplastics in an Alpine glacier environment (the Forni Glacier, a wide valley glacier located in the Italian Alps [20,21]), detecting concentrations comparable with those previously found in marine and coastal areas [18]. Crosta et al (2022) [22] found microplastics on other glaciers in the Italian Alps [22], suggesting the urgent necessity of actions to reduce the spread of microplastics in mountain glacierized areas.…”
Section: Introductionmentioning
confidence: 58%
“…The analyses presented in this study have in fact highlighted that the comparison of surface solar irradiance records from different data sources is a complex issue that has to be performed, critically evaluating the strengths and the weaknesses of each of them in relation to the objectives of the analysis. For example, a study has shown that short-and long-wave satellite data can be successfully used on a glacier surface to estimate summer glacier melting if they are not available from on-glacier surface measurements [60], even if satellite data at high-elevations present some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…1A). The detailed description of the Forni Glacier is provided in Azzoni et al (2016), Citterio et al (2007), and Senese et al (2020). We collected metazoans and cryoconite from cryoconite holes (Fig.…”
Section: Study Site and Samplingmentioning
confidence: 99%